The applications of vector calculus to the study of the temporal uniformity of development of socio-economic objects - Cheba, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
Dynamic changes observed on global markets mainly due to the economic slowdown but also as in the case of Japan the effect of natural disasters, are the main reason for the need to take into account the new operating conditions in global logistics strategies of corporations. They also have a direct impact on decisions concerning the location of foreign investment. One of the factors increasingly influencing the location decisions of investors is the stability of economic development measured not only in relation to that country, but also the entire geographic region. This is particularly important in the case of such political and economic structures like the European Union, bringing together countries with significant differences in levels of development and with different conditions and experiences of functioning. The aim of this study is to analyze the temporal uniformity of indicators which could determine the attractiveness (economic competitiveness), of the European Union as a place for the location of foreign investment. For the study of this temporal uniformity the calculus vector was used. The results confirmed the considerable temporal diversity of development of the analyzed indicators. Presented results are part of a research project called “Management methods in Japanese supply chains in Poland and the UK”, funded by the National Science Centre.